Audit Manajemen Dalam Menilai Efektivitas Atas Fungsi Sumber Daya Manusia Pada DP2KBP3A Kota Sukabumi - Lediyanti, Dila; Nugroho, Gatot Wahyu; Sudarma, Ade (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study aims to evaluate the effectiveness of human resource functions through management audits at the Population Control, Family Planning, and Women's Empowerment and Child Protection Agency (DP2KBP3A) of Sukabumi City. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research findings indicate that the audit process was conducted systematically by the Human Resources Development and Management Agency (BKPSDM). The implementation of human resource management functions has been carried out in accordance with regulations; however, issues such as inappropriate staff placement and work discipline were still identified. Follow-up actions include training for new employees and improving the supervision system; however, further refinement of policies and technology is still required. Overall, management audits play a crucial role in enhancing the effectiveness of human resource management within the DP2KBP3A of Sukabumi City.